Theoretical Media Economics Perspectives and Areas for Future Development in Malaysia - Vimala, Govindaraju; Shafinah Begum, Abdul Rahim (Hong Kong journal of Social Sciences, 2022)
This article aims to explore a literature review of theoretical media economics perspectives in the landscape of Malaysia. This article also focused on the successful scenario in national and international markets, economists' and business owners' understanding of the current economic trends in Malaysia. This article focuses on the theoretical aspects of media economics from the Malaysian perspective. It is presented in four mutually inclusive sections: (a) firm decisions and consumers' media access; (b) a better understanding of Malaysia's microeconomic and macroeconomic theoretical perspectives; (c) cultural economy and development; (d) a brief review of Malaysia's future development sectors. This will enable them to contribute to the economic changes required for Malaysia to strengthen its resilience further. The subject matter of media economics is evolving in popularity, as evidenced by the emergence of publications dedicated to the area, the expansion in literature base, and increased interest among academics. In light of its development, media economics continues to be a topic of discussion that goes hand in hand with the advancement in technology and innovation and the interactions between the local and international markets.